2015
DOI: 10.1007/978-3-319-18365-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phenolic Compounds as Therapeutic and Preventive Agents for Cerebral Amyloidosis

Abstract: Epidemiological studies have suggested that diets rich in phenolic compounds may have preventive effects on the development of dementia or Alzheimer's disease (AD). We investigated the effects of natural phenolic compounds, such as myricetin (Myr), rosmarinic acid (RA), ferulic acid (FA), curcumin (Cur) and nordihydroguaiaretic acid (NDGA) on the aggregation of amyloid β-protein (Aβ), using in vitro and in vivo models of cerebral Aβ amyloidosis. The in vitro studies revealed that these phenolic compounds effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 121 publications
2
52
0
Order By: Relevance
“…Elevated intake of dietary polyphenols might be relevant to the prevention of amyloidosis. Nutraceutical strategies might become a way to reduce the risk of certain amyloid diseases [19,21]. Many drugs used today are natural products or derivatives of natural products [22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated intake of dietary polyphenols might be relevant to the prevention of amyloidosis. Nutraceutical strategies might become a way to reduce the risk of certain amyloid diseases [19,21]. Many drugs used today are natural products or derivatives of natural products [22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Several biological activities are attributed to RA, such as antioxidant and anti-inflammatory properties and neuroprotective effects [26][27][28][29][30] . RA has been proven to be effective in experimental models of neurodegenerative diseases such as Alzheimer disease and amyotrophic lateral sclerosis [31,32] , and recently it was shown to have the interesting effect of reducing seizures in rats [27,[33][34][35] . A previous study showed that RA inhibits the activity of GABA-T.…”
mentioning
confidence: 99%
“…38 Similar anti-amyloidogenic effects were also reported in studies with mice for 1 , 3 , and 11 , supporting the potential preventive properties of these natural compounds against AD. 39 …”
Section: Resultsmentioning
confidence: 99%